How Does Occupational Lifting Affect Ambulatory Blood Pressure, Relative Aerobic Workload and Level of Physical Activity? - Baumann, Mathilde; Poulsen, Martine Mejding; Mortensen, Ole Steen; Olsen, Michael Hecht; Korshøj, Mette (Annals of Work Exposures & Health, 2023)
Introduction Occupational physical activity (OPA), including occupational lifting (OL), seems to increase the risk of cardiovascular disease (CVD). Knowledge about the association between OL and risk of CVD is sparse, but repeated OL is assumed to result in prolonged raised blood pressure and heart rate (HR) eventually augmenting the risk of CVD. To disentangle parts of the mechanisms behind the raised 24-hour ambulatory blood pressure measurement (24h-ABPM), by exposure to OL, this study aimed to explore the acute differences in 24h-ABPM, relative aerobic workload (RAW) and OPA across workdays with and without OL, and secondary to assess the feasibility and rater agreement of direct field observations of the frequency and load of occupational lifting. Methods This controlled cross-over study investigates associations between moderate to high OL and 24h-ABPM, RAW in per cent of heart rate reserve (%HRR) and level of OPA. This included 2x24h monitoring of 24h-ABPM (Spacelabs 90217), PA (Axivity) and HR (Actiheart), comprising a workday containing OL and a workday without. The frequency and burden of OL were directly observed in field. The data were time synchronized and processed in the Acti4 software. Differences across workdays with and without OL in 24h-ABPM, RAW and OPA were evaluated using repeated 2 × 2 mixed-models among 60 blue-collar workers in Denmark.. Exposure to OL was estimated by direct manual field observation, registering burden and frequency of OL. Interrater reliability tests were performed across 15 participants representing 7 occupational groups. Interclass correlation coefficient (ICC) estimates of total burden lifted and frequency of lifts were calculated, based on a mean-rating (k = 2), absolute-agreement, 2 way mixed-effects model, indicating the raters as fixed effects. Results OL led to non-significant increases in ABPM during work-time (systolic Δ1.79 mmHg, 95%CI −4.49–8.08, diastolic Δ0.43 mmHg, 95%CI −0.80–1.65), and on 24-hours basis (systolic Δ1.96 mmHg, 95%CI −3.80–7.72, diastolic Δ0.53 mmHg, 95%CI −3.12–4.18), significant increases in RAW during work (Δ7.74 %HRR, 95%CI 3.57–11.91) as well as a raised level of OPA (Δ4156.88 steps, 95%CI 1898.83–6414.93, Δ−0.67 hours of sitting time, 95%CI −1.25–0.10, Δ−0.52 hours of standing time, 95%CI −1.03–0.01, Δ0.48 hours of walking time, 95%CI 0.18–0.78). ICC estimates were 0.998 (95% CI 0.995–0.999) for total burden lifted and 0.992 (95% CI 0.975–0.997) for frequency of lift. Discussion OL increased both intensity and volume of OPA among blue-collar workers, which supposedly to contributes to an augmented risk of CVD. Although this study finds hazardous acute effects, further investigations are needed to evaluate the long-term effects of OL on ABPM, HR and volume of OPA, also effects of cumulative exposure to OL would be relevant to investigate. Conclusion OL significantly raised the intensity and volume of OPA. Direct field observation of occupational lifting showed an excellent interrater reliability.